2010
DOI: 10.1007/s11136-010-9599-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the use of health-related quality of life measures in the routine clinical care of lung-transplant patients

Abstract: We detected very small effects on patient-clinician communication and small effects on patient management, without detecting improvement in patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 25 publications
0
67
1
Order By: Relevance
“…The training session for transplant specialists was designed for a randomized trial where chronic lung disease patients completed the Health Utilities Index (HUI) at every outpatient visit and the graphically presented results were shared with clinicians [23][24][25] . At every visit, discussions amongst patient, family and team members were audio-recorded to assess communication, the role of HUI and how the information contributed to care plans.…”
Section: Clinical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The training session for transplant specialists was designed for a randomized trial where chronic lung disease patients completed the Health Utilities Index (HUI) at every outpatient visit and the graphically presented results were shared with clinicians [23][24][25] . At every visit, discussions amongst patient, family and team members were audio-recorded to assess communication, the role of HUI and how the information contributed to care plans.…”
Section: Clinical Settingmentioning
confidence: 99%
“…The quick card was tailored to team needs and to the size of their white coats pockets. [23][24][25] Monitoring PROs use During the first month, clinicians completed the proxy version at every visit after seeing icians scored patients lower than the patients themselves, proving the importance of adding the patient perspective. Subsequently, at the monthly team rounds the use of PROs was reinforced by presenting clinical cases to encourage adoption and respond to queries.…”
Section: Content and Supporting Materialsmentioning
confidence: 99%
“…While some studies find no effects [2,29,3], others provide limited evidence of improved wellbeing [4,16,11]. It is arguable that understanding one's own QoL does not necessarily lead to change at the time it is received, and the majority of intentions to adopt new behaviours are not always followed by actual behaviour change [30].…”
Section: Discussionmentioning
confidence: 99%
“…It is also plausible that not using diseasespecific measures may have made a difference to our ill sample, as these are generally found to be more responsive to change (Santana et al, 2010), but this would neither have been practicable, nor enabled us to test the generic principle of the impact of QoL feedback.…”
Section: Discussionmentioning
confidence: 99%
“…This represents an intervention in its own right, and evidence for its efficacy is contradictory. While some studies found no effects (Hilarius et al, 2008;Rosenbloom et al, 2007;Santana et al, 2010), others provide limited evidence of positive outcomes such as improved emotional wellbeing (Velikova et al, 2004), disease-specific QoL and mental QoL (Gutteling et al, 2008), behavior, psychosocial health and family activities (De Wit et al, 2008). Although indicating that QoL feedback is an important mechanism whereby wellbeing can be influenced, the exact process remains unclear, as feedback methods vary widely.…”
Section: Introductionmentioning
confidence: 99%